Differences in Lead Levels on Doors and Walls of Children's Homes: A Cross-sectional Study in Java, Indonesia - Agus Kharmayana Rubaya; Sarjito Eko Windarso; Haryono Haryono; Sigid Sudaryanto; Muchtaruddin Mansyur; Tantut Susanto (JURNAL INFO KESEHATAN, 2025)
Children are one of the most vulnerable groups to lead exposure. Exposure in children is primarily related to hand-to-mouth activities and environmental conditions. Studies on lead level in homes measurements, which are linked to blood lead levels in children, are still rare. The objective of the study was to identify lead levels on painted surfaces, consisting of doors and walls, in the homes of children aged 12-59 months who had high blood lead levels (≥ 20 μg/dl). The method was a cross- sectional study conducted in Java, Indonesia, comparing lead exposed and unexposed in areas with battery recycling activities to a demographically similar control area without such activities (Cinangneng-Bogor). The results showed among the 145 inspected homes in the exposed areas, 40 were measured on doors and 93 on walls; meanwhile among the 240 inspected homes in the unexposed areas, 35 were measured on doors and 36 on walls. In the exposed areas, the lead levels at the door ranged from 0.00 µg/cm2 – 891.36 µg/cm2 and it was not different (p = 0,671) from that in the unexposed areas, i.e. ranged from 0.00 µg/cm2 – 537.03 µg/cm2. Meanwhile, the lead levels at the walls in the exposed areas were measured ranged from 0.00 µg/cm2 – 279.21 µg/cm2 (median 0.65 µg/cm2), and it was significantly different (p <0.001) from that in the unexposed area, i.e. ranged from 0.00 µg/cm2 – 45.64 µg/cm2 (median 0.00 µg/cm2). The findings of lead exposure in the children’s homes lead to a strong recommendation to regulate the elimination of lead in the household paints, and to escalate community concern of domestic lead hazards.